Use of mechanical refining to improve the production of low-cost sugars from lignocellulosic biomass. (January 2016) - Park, Junyeong; Jones, Brandon; Koo, Bonwook; Chen, Xiaowen; Tucker, Melvin; Yu, Ju-Hyun; Pschorn, Thomas; Venditti, Richard; Park, Sunkyu
Highlights: Mechanical refining is a viable technology to produce low-cost sugars. Carbohydrate conversion can be enhanced with lower loading of enzymes. Pretreatment severity can be reduced to achieve the similar level of conversion. Mechanical refining is relatively less energy dependent, with high throughput. Abstract: Mechanical refining is widely used in the pulp and paper industry to enhance the end-use properties of products by creating external fibrillation and internal delamination. This technology can be directly applied to biochemical conversion processes. By implementing mechanical refining technology, biomass recalcitrance to enzyme hydrolysis can be overcome and carbohydrate conversion can be enhanced with commercially attractive levels of enzymes. In addition, chemical and thermal pretreatment severity can be reduced to achieve the same level of carbohydrate conversion, which reduces pretreatment cost and results in lower concentrations of inhibitors. Refining is versatile and a commercially proven technology that can be operated at process flows of ∼1500 dry tons per day of biomass. This paper reviews the utilization of mechanical refining in the pulp and paper industry and summarizes the recent development in applications for biochemical conversion, which potentially make an overall biorefinery process more economically viable.